Alexithymia in eating disorders: Systematic review and meta-analyses of studies using the Toronto Alexithymia Scale - Westwood, Heather; Kerr-Gaffney, Jess; Stahl, Daniel; Tchanturia, Kate (Journal of psychosomatic research, 2017)
The aim of this review was to synthesise the literature on the use of the Toronto Alexithymia Scale (TAS) in eating disorder populations and Healthy Controls (HCs) and to compare TAS scores in these groups. Electronic databases were searched systematically for studies using the TAS and meta-analyses were performed to statistically compare scores on the TAS between individuals with eating disorders and HCs. Forty-eight studies using the TAS with both a clinical eating disorder group and HCs were identified. Of these, 44 were included in the meta-analyses, separated into: Anorexia Nervosa; Anorexia Nervosa, Restricting subtype; Anorexia Nervosa, Binge-Purge subtype, Bulimia Nervosa and Binge Eating Disorder. For all groups, there were significant differences with medium or large effect sizes between the clinical group and HCs, with the clinical group scoring significantly higher on the TAS, indicating greater difficulty with identifying and labelling emotions. Across the spectrum of eating disorders, individuals report having difficulties recognising or describing their emotions. Given the self-report design of the TAS, research to develop and evaluate treatments and clinician-administered assessments of alexithymia is warranted. •Individuals across the spectrum of eating disorders have difficulties identifying and describing emotion•Studies examining alexithymia in individuals with Binge Eating Disorder and those recovered from eating disorders are lacking•Research on alexithymia would benefit from the development of clinically-based assessment tools